Evaluation of knowledge and use of nutritional labeling in packaged food and/or bottled beverages products among adolescents and adults in Antioquia in 2019 (2023)
ABSTRACT: Introduction: Nutritional labeling (NL) is a fundamental component of the informative food environment and constitutes a health promotion tool whose purpose is to guide the consumers of packaged food and/or bottled beverages products (PFBBP) in their purchase decision. Objectives: To document the knowledge, use, and perception of the available information in the current NL in the PFBBP, as well as its impact on the decision to purchase products. Methods: The study was carried out based on the Food and Nutritional Profile of Antioquia (Perfil Alimentario y Nutricional de Antioquia - PANA) 2019. This study was population-based, descriptive, and cross-sectional, with a probabilistic, stratified, and multi-stage design that involved the NL subcomponent. Study population: person in charge of purchasing food at home and adolescents between 10-17 years old. A survey with eleven questions was used, accompanied by two model boxes as a didactic and facilitating strategy: one designed according to Colombian regulations and the other with front-of-package labeling that consisted of an octagonal warning message. Descriptive statistics were calculated using the R software. Results: The 78.0% of those surveyed do not know how many calories they should consume per day. Although approximately 92.7% (95% CI 92.6-92.7) stated that they knew how to read and write, only 48.5% (95% CI 48.3-48.7) stated that they read the information on the PFBBP’s packaging. Regarding which label they consult and use to decide the purchase, the most frequent response was the expiration date. Regarding the acceptance of the use of front-of-package labeling when the content of calories, sugar, salt, or fat was excessive (associated with risk of disease), acceptance was found in 95.8% of the respondents (CI 95% 94, 9-96.6). Conclusions: The current NL in Colombia is not easy to read or use by the majority of the people surveyed in the PANA, therefore, it does not facilitate the purchase decision. The implementation of front-of-package labeling that is easy to read and comprehend, and free of conflicts of interest is a priority, following the recommendations of international organizations such as PAHO and WHO. Conflict of Interest: The authors declare no conflict of interest.